Changes in neuroendocrine elements in bronchial mucosa in chronic lung disease in adults. Issue 5 (May 1995) - Pilmane, M; Luts, A; Sundler, F
Abstract : BACKGROUND–It is not clear whether there is any association between metaplasia of the bronchial epithelium and changes in the distribution of neuroendocrine cells. This study examined, by immunohistological techniques, the distribution of neuroendocrine cells and juxtamucoscal nerve fibres in bronchial biopsies showing metaplastic changes. METHODS–Bronchial biopsies from 12 subjects with epithelial metaplasia associated with bronchiectasis and diffuse pulmonary fibrosis were examined by conventional light microscopy and immunohistological techniques for protein gene product 9.5 (PGP), chromogranin A and B (CAB), serotonin, vasoactive intestinal peptide (VIP), substance P (SP), calcitonin gene-related peptide (CGRP), calcitonin (CT), and gastrin releasing peptide (GRP). RESULTS–Regions of non-metaplastic epithelium contained numerous PGP and serotonin immunoreactive cells. Sub-populations of these cells displayed CAB, CGRP, CT, and GRP immunoreactivity. Metaplastic epithelium contained only a few weakly stained PGP, serotonin, CAB, GRP, CT and CGRP immunoreactive cells in six cases. Metaplastic epithelium was characterised by a high number of CAB-containing cells in six cases and in these biopsies prominent PGP-containing nerve bundles were seen in the subepithelial layer beneath the metaplastic epithelium. CONCLUSIONS–The distribution patterns of neuroendocrine cells and neuronal elements vary between areas of normal and metaplastic epithelium and within areas of metaplastic epithelium. Neuronal hyperplasia was associated with an increase in the number of CAB-containing cells within the metaplastic epithelium.